Turkish nurses' assessments of their power and the factors that affect it. (3rd September 2014) - Basaran, Seher; Duygulu, Sergul
Abstract : Aim: To explore nurses' self‐assessments of power and their opinions regarding factors affecting power in Turkey using a cross‐sectional, descriptive study. Background: In order to safely and cost‐effectively care for patients, nurses must perceive themselves as powerful and have the use and control of power resources. Method: The study sample consisted of 297 nurses in six hospitals: two government hospitals, two university hospitals and two private hospitals. Data were collected using the Demographic Data Form and Power Question Form. Results: Nurses regarded themselves as 'quite powerful' regarding persuasion (53.2%) and referent power (43.4%). Many nurses also regarded themselves as having positional power and 'quite powerful' regarding, reward (44.1%) and legitimate power (34.7%). Nurses saw themselves as least powerful in resource power (48.1%). Individual, educational and organisational factors were the main factors affecting personal and positional power sources. Conclusion: Turkish nurses regarded themselves as above average on being powerful in both the personal and positional power base but not in resource power. Implications for nursing management: We recommend that nurses, educators and managers develop strategies to support nurses' power as a way to enhance the patient care outcomes.